PROMOTING LEARNER AUTONOMY IN EFL WRITING CLASSROOMS (Journal of Foreign Language Studies, 2024)
In any process of learning, learner plays the most important role among such factors as teacher, learner, course material and teaching methods. In other words, learners who want to be successful in the learning process need to take charge of their own learning. Therefore, it is important for learners, especially those of English as a foreign language to have great autonomy in learning. It is also important for teachers to promote the learner autonomy in English classrooms in general and English writing classrooms in particular. As writing is a productive skill, learners in English writing classes should be encouraged to be autonomous and given more opportunities to think critically, to initiate learning and express themselves. This paper aims at discussing the concepts of learner autonomy, and the roles of teacher and learner in an autonomous classroom. Furthermore, it suggests ways to promote learner autonomy in learning writing skill.
Keywords: autonomy; writing skill